2000
DOI: 10.1080/00087114.2000.10589207
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of three Physalaemus species (Amphibia, Anura)

Abstract: Physalaemus biligonigerus, P. fuscomaculatus and P. sp. have 2n=2 chromosomes, consistent with the number of chromosomal pairs found in the genus. There were no substantial differences in the karyotypes of the three species, except for chromosome 3 which was submetacentric in P. fuscomaculatus and metacentric in P. biligonigerus and P. sp. All chromosomes were characterised by the presence of a C-band in the pericentromeric region. Some interstitial bands were also detected at the same position in all karyotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 20 publications
3
29
0
7
Order By: Relevance
“…This C-band was also observed in some specimens of P. cuvieri, especially in specimens collected in Palmeiras, state of Bahia, Brazil (Quinderé et al 2009). Although conspicuous in P. ephippifer, this band was not as large as previously described in P. biligonigerus and P. marmoratus (Amaral et al 2000), which are currently allocated to the P. albifrons group, or in Eupemphix nattereri, a genus closely related to Physalaemus. Interestingly, the 5S rDNA genes were located at the same chromosomal site as the P. ephippifer karyotype.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This C-band was also observed in some specimens of P. cuvieri, especially in specimens collected in Palmeiras, state of Bahia, Brazil (Quinderé et al 2009). Although conspicuous in P. ephippifer, this band was not as large as previously described in P. biligonigerus and P. marmoratus (Amaral et al 2000), which are currently allocated to the P. albifrons group, or in Eupemphix nattereri, a genus closely related to Physalaemus. Interestingly, the 5S rDNA genes were located at the same chromosomal site as the P. ephippifer karyotype.…”
Section: Discussionmentioning
confidence: 49%
“…Among the species of Physalaemus already studied cytogenetically (de Lucca 1974;Silva et al 1999Silva et al , 2000Amaral et al 2000;Quinderé et al 2009;Tomatis et al 2009;Milani et al 2010), P. ephippifer is the first case of heteromorphic sex chromosomes. This implies that the sex chromosome differentiation is a recent evolutionary event in Physalaemus and that it occurred after the divergence of the species.…”
Section: Discussionmentioning
confidence: 95%
“…The diploid number of the five Engystomops species studied here was 2n = 20, the same 2n reported previously for E. pustulatus and E. puyango (Ron et al 2010 Silva et al 1999Silva et al , 2000Amaral et al 2000;Quinderé et al 2009;Tomatis et al 2009;Milani et al 2010;Nascimento et al 2010), which is considered to be the sister-group of Engystomops (Ron et al 2006;Nascimento et al 2005). Therefore, we conclude that the 2n reduction from 2n = 22 to 2n = 20 is a synapomorphy of Duovox clade of Engystomops.…”
Section: Discussionmentioning
confidence: 70%
“…By comparing the 2n = 20 karyotypes of the species of the Duovox clade with the 2n = 22 karyotypes of E. freibergi, of E. petersi from Puyo (Targueta et al 2010) and of Physalaemus species (De Lucca et al 1974;Silva et al 1999Silva et al , 2000Amaral et al 2000;Quinderé et al 2009;Tomatis et al 2009;Milani et al 2010;Nascimento et al 2010), a great similarity can be identified for the seven first chromosome pairs. Despite that, the chromosomal data already available does not allow us to infer any chromosomal loss or rearrangement that might have resulted in the 2n reduction in the Duovox clade.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation